Increasing Conceptual Understanding through CCM-CCA Based Learning Device - Muh. Makhrus; Muhammad Zuhdi; Wahyudi Wahyudi; Muhammad Taufik (Postgraduate, University of Mataram, 2020)
Learning must be focus on creating conceptual change in students. One of the alternatives is using CCM-CCA-based learning devices because CCM-CCA is a learning model that can create cognitive conflict as a condition for conceptual change. This research is directed to develop learning devices based on CCM-CCA that can improve conceptual understanding. The learning devices developed to consist of LEU (Learning Events Units) and SW (Students’ Worksheet) for Newton's Law material about motion and work-energy. The results of the validation of learning devices (LEU and SW validation) indicate that these devices are valid in content and construction so that they are suitable for the learning process. Based on the results of the implementation of the device and the test results, it was concluded that the CCM-CCA-based learning device was able to improve conceptual understanding. The increase was obtained through an N-Gain analysis with an N-Gain value for LEU of 60.44% and SW of 54.01%. The percentage of the N-Gain score is included in the increase with the medium category.